2007
DOI: 10.1094/pdis-91-9-1161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Field, Greenhouse, and Detached-Leaf Evaluations of Soybean Germplasm for Resistance to Phakopsora pachyrhizi

Abstract: Fourteen soybean accessions and breeding lines were evaluated for resistance to soybean rust caused by the fungus Phakopsora pachyrhizi. Evaluations were conducted in replicated experiments in growth chambers using detached leaves and under greenhouse and field conditions. In growth-chamber experiments, inoculation of detached leaves with 1 × 106 spores/ml resulted in a significantly (P < 0.0001) higher total number of pustules and spores per unit leaf area than inoculations with lower spore concentrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 23 publications
3
45
1
4
Order By: Relevance
“…Management strategies such as the use of fungicides, the adoption of a free host period, and the use of genetic resistance are important for controlling ASR (Yorinori 2008). The development of soybean varieties resistant to ASR is considered the most economical control strategy; therefore it is important to facilitate its management (Twizeyimana et al 2007, Pierozzi et al 2008. However, resistance is not always durable due to pathogen variability (Oliveira et al 2005), and there is a large regional pathogenic diversity in the ASR pathogen population in Brazil (Freire et al 2008, Kato and Yorinori 2008, Soares et al 2009, Akamatsu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Management strategies such as the use of fungicides, the adoption of a free host period, and the use of genetic resistance are important for controlling ASR (Yorinori 2008). The development of soybean varieties resistant to ASR is considered the most economical control strategy; therefore it is important to facilitate its management (Twizeyimana et al 2007, Pierozzi et al 2008. However, resistance is not always durable due to pathogen variability (Oliveira et al 2005), and there is a large regional pathogenic diversity in the ASR pathogen population in Brazil (Freire et al 2008, Kato and Yorinori 2008, Soares et al 2009, Akamatsu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sterilization of leaf samples reduced the saprophytic populations and similarly [13]. Antimicrobial peptide genes have high antimicrobial activity against various pathogenic fungi and are the potential genes to be transformed into plants for transgenic development [14] [2]. In the present study, transgenic plant 10-7 showed higher resistant and moderate resistant was observed in 7-2, 13-19 and 1-3 when compared to the other lines.…”
Section: Discussionmentioning
confidence: 53%
“…Nonetheless, despite these inconsistencies there was overall a good correlation between leaf-disk and field results. Detached-leaf bioassays have also been shown to produce results comparable to assays performed using whole plants in a growth chamber or greenhouse during screening of soybean genotypes with the rust Phakopsora pachyrhizi (Twizeyimana et al 2007) and oat cultivars with Puccinia coronata (Jackson et al 2008).…”
Section: Discussionmentioning
confidence: 99%